“The Impact of Visual Arts Education on Students’ Creative and Cognitive Development in Schools and Universities” - Aslonova Shaxnoza Islom qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the influence of visual arts education on students’ creative and cognitive development in school and higher education. It emphasizes how early exposure to visual arts enhances observation, critical thinking, and imaginative skills, while higher education further refines these abilities through advanced projects and interdisciplinary approaches. The study highlights the importance of integrating visual arts across educational levels to foster holistic development and prepare students for creative careers.